2021
DOI: 10.1016/j.ijnss.2020.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and evaluation of a pain management core competency education program for surgical nurses

Abstract: Objective To investigate the effect of a pain management core competency education program on surgical nurses’ pain knowledge and pain management nursing practice behaviors. Methods An 8-h education program focused on pain management core competency was provided twice in two weeks including the multidimensional nature of pain, pain assessment, pharmacological and non-pharmacological management, and knowledge application was developed and implemented for surgical nurses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The results showed that nurse's knowledge in the intervention group increase 11% (p=0,009) compared to the time before the intervention [25] . In addition, other semi-empirical studies were conducted in China also found that nurses who had received pain management education had significantly higher mean knowledge scores than before intervention (45.6% ± 12.3% to 54 .2% ± 10.2% ((t = 5.786, p < 0.001) [26] .…”
Section: Discussionmentioning
confidence: 84%
“…The results showed that nurse's knowledge in the intervention group increase 11% (p=0,009) compared to the time before the intervention [25] . In addition, other semi-empirical studies were conducted in China also found that nurses who had received pain management education had significantly higher mean knowledge scores than before intervention (45.6% ± 12.3% to 54 .2% ± 10.2% ((t = 5.786, p < 0.001) [26] .…”
Section: Discussionmentioning
confidence: 84%
“…Many tonsillectomy patients are reluctant to eat or eat less after surgery due to pain, which affects their nutritional intake, and insufficient nutritional intake not only affects the patient's recovery and increases the probability of complications, but also prolongs the patient's hospitalisation time and increases hospitalisation costs 6 . With the development of nursing, the role of nursing in the management of postoperative pain has gradually gained clinical recognition 31 . Although conventional postoperative nursing care can help patients recover after surgery, it still fails to achieve satisfactory results in relieving postoperative pain, improving nursing satisfaction and shortening the total length of hospital stay 32 .…”
Section: Discussionmentioning
confidence: 99%
“…6 With the development of nursing, the role of nursing in the management of postoperative pain has gradually gained clinical recognition. 31 Although conventional postoperative nursing care can help patients recover after surgery, it still fails to achieve satisfactory results in relieving postoperative pain, improving nursing satisfaction and shortening the total length of hospital stay. 32 As the comprehensive postoperative nursing is more targeted to the patient's care service, it makes up for the shortcomings of conventional care.…”
Section: Discussionmentioning
confidence: 99%
“…It can not only observe tissue edema and vessel diameter, but also dynamically observe arterial pulsation and fascial tissue elasticity changes. Related scholars have studied the pulsed phase-locked loop ultrasound instrument to observe the fascia displacement waveform of the arterial blood pressure pulse to estimate the pressure of the osteofascial compartment [8]. The correlation between the degree of fascia displacement in the osteofascial compartment and the perfusion pressure was confirmed by the researchers through noninvasive ultrasound.…”
Section: Related Workmentioning
confidence: 95%